Expert Answers

An illustration of the letter 'A' in a speech bubbles

ln (x+2) - ln 3x = ln 5

We know that :

ln a - ln b = ln a/b

==> ln (x+2)- ln 3x = ln (x+2)/3x = ln 5

==> (x+2)/3x = 5

Now cross multiply:

==> x+2 = 15x

==> 13x = 2

==> x = 2/13

Approved by eNotes Editorial Team
Soaring plane image

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial